PHQ-9: Validation and Investigation Response Format using Nominal Response Model - Marvianto, Ramadhan Dwi; Kusrohmaniah, Sri (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2025)
The Patient Health Questionnaire 9 (PHQ-9) is a widely used tool for depression screening, but its internal structure varies across different contexts and potentially leads to misinterpretations of the depression construct it measures. This study aims to investigate the internal structure and response format effectiveness of the Indonesian version of the PHQ-9. Data were collected from 1,310 participants who completed the PHQ-9 questionnaire, sourced from the Faculty of Psychology of the Universitas Gadjah Mada (UGM)’s database. Data analysis included confirmatory factor analysis (CFA), item factor analysis (IFA), and item response theory (IRT) using a nominal response model (NRM). Results indicated that a two-factor model demonstrated a better fit than a single-factor model, which was categorised as a marginal fit. Furthermore, nearly all items functioned effectively in their response format, except for items 5 (poor appetite) and 9 (suicidal thoughts), which showed suboptimal functioning in the highest categories. These findings support the practical use of the PHQ-9 and underscore the value of collapsing categories when extreme responses are rarely endorsed to improve measurement precision.